2017
DOI: 10.1002/mrd.22806
|View full text |Cite
|
Sign up to set email alerts
|

Conserved insulin signaling in the regulation of oocyte growth, development, and maturation

Abstract: Insulin signaling regulates various aspects of physiology, such as glucose homeostasis and aging, and is a key determinant of female reproduction in metazoans. That insulin signaling is crucial for female reproductive health is clear from clinical data linking hyperinsulinemic and hypoinsulinemic condition with certain types of ovarian dysfunction, such as altered steroidogenesis, polycystic ovary syndrome, and infertility. Thus, understanding the signaling mechanisms that underlie the control of insulin-media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
98
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(105 citation statements)
references
References 163 publications
2
98
0
1
Order By: Relevance
“…Hypothesis 3a: While we have rather limited evidence on birds (see above), IGF-1 has been shown to have an important role in the regulation of reproduction in nematodes, insects, fish and mammals (e.g. mice and humans) (Baker et al, 1996;Daftary & Gore, 2005;Das & Arur, 2017;Flatt & Heyland, 2011). Therefore, we expected a positive association between IGF-1 levels and variables of reproductive investment, such as mean egg weight and clutch size;…”
Section: Reproductive Investmentmentioning
confidence: 98%
“…Hypothesis 3a: While we have rather limited evidence on birds (see above), IGF-1 has been shown to have an important role in the regulation of reproduction in nematodes, insects, fish and mammals (e.g. mice and humans) (Baker et al, 1996;Daftary & Gore, 2005;Das & Arur, 2017;Flatt & Heyland, 2011). Therefore, we expected a positive association between IGF-1 levels and variables of reproductive investment, such as mean egg weight and clutch size;…”
Section: Reproductive Investmentmentioning
confidence: 98%
“…Numerous studies indicated that metabolic hormones, such as insulin (Das & Arur, 2017), ghrelin (Dovolou et al, 2014), kisspeptin (Kasum et al, 2017), leptin (Craig, Zhu, Dyce, Petrik, & Li, 2004), have been found to play an important role in oocyte maturation and development by the regulation of energy balance.…”
Section: Introductionmentioning
confidence: 99%
“…The IIS pathway is an evolutionarily conserved nutrientsensing pathway that modulates various aspects of physiology, such as metabolism, longevity, and development, and plays a key role in female reproduction in metazoans (Taniguchi et al, 2006;Wu and Brown, 2006;Hietakangas and Cohen, 2009;Das and Arur, 2017). Genetic evidence from Drosophila melanogaster shows that the InR mutant yields dwarf females with arrested egg development at the previtellogenic stage (Tatar et al, 2001).…”
Section: Introductionmentioning
confidence: 99%